Service quality and customer satisfaction in transport service industry in Tanzania : A case of Dar express bus company - Mushi, Onael W. (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the Degree of Master of Business Administration (MBA) of Mzumbe University.